Portfolio optimization: An overview of integrated approaches and mathematical programing techniques - Mishra, D.K.; Shinde, Vikas; Wadhwa, Kamal; Chaudhary, Sanjay (The journal of contemporary issues in business and government, 2021)
Selection of stocks is a challenging task for investors and finance researchers because of the uncertainty of the return. In portfolio selection, the aim is to obtain a proper proportion of assets for getting maximum profit and least risk. The objective of his paper is to provide an overview of the present research in portfolio optimization with respect in mathematical programing techniques. For this purpose, 82 research papers appearing in the scholarly journal have been observed and investigated, and it has been concluding that fuzzy decision theory and goal programming establish the maximum number of mathematical programming techniques generated to solve the portfolio optimization problem.